STATISTICAL ANXIETY OF STUDENTS IN PANDEMIC ERA - Deni Iriyadi (Jurnal Evaluasi Pendidikan, 2022)
This study aims to see how the statistical comparison of students who have not and have taken statistics courses for non-exact students. This research is a quantitative research with a survey approach. The instrument in this study adopted the Statistical Anxiety Scale (SAS) which consists of 3 components (worry, avoidance, emotionality) with a total of 17 items with 4 scales. Respondents in this study were students of the State Islamic University of Sultan Maulana Hasanuddin Banten in the first semester until the end of the semester. The number of samples in this study was 238. The results showed that there was no difference between the anxiety of students who had not and had taken course statistics. Nevertheless, descriptively the probability of changes in student statistics between before and after taking statistics courses. At the rate of increase the percentage decreases while at the rate of increase the percentage decreases. This shows a change in student statistics after taking statistics lessons, especially in the pandemic era by still using a bold learning system